Efektivitas Layanan Informasi dengan Pendekatan Cooperative Learning Model Jigsaw untuk Membentuk Sikap Anti Cyberbullying Siswa - Sofia, Siti; Sukmawati, Indah (YASIN, 2024)
This research is motivated by the phenomenon where there are still students who send harsh words through conversations on social media, humiliate friends by editing and spreading their personal photos on social media, so it can be said that students don’t have anti-cyberbullying attitudes. As a student, an anti-cyberbullying attitude should be possessed, in order to help create a safe and comfortable learning atmosphere where all students feel valued and protected. Therefore, information services with jigsaw-type cooperative learning approach are needed to shape students' anti-cyberbullying attitudes. This type of research uses quantitative approach with a pre-experimental method of one group pretest and posttest design. The subjects of this study amounted to 30 students of class XI SMAN 1 Lubuk Basung. Subjects selection using purposive sampling technique. The data collection technique used an anti-cyberbullying attitude scale, the data were analyzed using the Wilcoxon signed rank test. The results showed that information services with a jigsaw-type cooperative learning approach were effective for forming anti-cyberbullying attitudes in students, where after being given the treatment, students' anti-cyberbullying attitudes increased significantly. This can be seen from the results of hypothesis testing, the Asymp.Sig (2-tailed) result of anti-cyberbullying attitudes in students is 0.000, in other words, the probability is below 0.05 (0.000 ≤ 0.05), meaning that H0 is rejected and Ha is accepted. Based on these results, it is concluded that information services with a jigsaw-type cooperative learning approach are effective for forming anti-cyberbullying attitudes in students.